PENGARUH PROGRAM AKSELERASI TAHFIDZUL QURAN DAN MOTIVASI BELAJAR TERHADAP PRESTASI AKADEMIK SISWA - Muslih, Ahmad Muslih; Rena, Syahidah; Pahrurraji (Cattleya Darmaya Fortuna, 2024)
Since reading, memorizing, and practicing the Al-Quran is the road to happiness for every Muslim in this life and the next, many Islamic educational institutions are currently attempting to encourage their students to engage with it more. Islamic educational institutions work to enhance student accomplishment by raising motivation through a variety of initiatives, in addition to enhancing the Al-Qur'an curriculum, in order to maximize the attainment of learning objectives. This thesis aims to analyze the effects of learning motivation and the Tahfidzul Quran Acceleration program on the academic achievement of Ma'had Rahmaniyah Al-Islamy students in Bogor. Additionally, it analyzes the joint effects of these two factors on the academic achievement of Ma'had Rahmaniyah Al-Islamy students in Bogor. Research using quantitative descriptive analysis is included in this study. To evaluate preconceived ideas, data gathering methods include research tools, quantitative/statistical data analysis, and supplementary interviews with relevant parties. Based on the research findings, it can be said that the Tahfidzul Quran Acceleration Program and Learning Motivation have a significant positive impact on the academic achievement of Ma'had Rahmaniyah Al-Islamy Cibinong Bogor students. Additionally, there is a significant positive impact on the academic achievement of Ma'had Rahmaniyah Al-Islamy Cibinong Bogor students when both programs are implemented concurrently.